Inverse dynamic analysis of shoulder muscle activity during archery draw back - Reddy, A.; Al-Smad, Y. M. (Proceedings of the ASME 2015 International Mechanical Engineering Congress and Exposition. Volume 3: Biomedical and Biotechnology Engineering. Houston, Texas, USA. November 13-19, 2015, 2015)
The objective of this study is to conduct biomechanical simulation for a musculoskeletal of archery performance. The simulation aims to find the movement patterns in working postures, the muscle activity and joint reaction forces. The results obtained are discussed and the work presented can help analyze the utilization of various muscles during the performance of the repetitive motion of archery.